2017
DOI: 10.31768/2312-8852.2017.39(2):106-111
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF EXOGENOUS LACTOFERRIN ON THE OXIDANT/ ANTIOXIDANT BALANCE AND MOLECULAR PROFILE OF HORMONE RECEPTOR-POSITIvE AND -NEGATIvE HUMAN BREAST CANCER CELLS IN VITRO

Abstract: Aim: To investigate the mechanisms of cytotoxic activity and pro-/antioxidant effect of lactoferrin on hormone receptor-positive and receptor-negative breast cancer cells in vitro. Materials and Methods: The study was performed on receptor-positive (MCF-7, T47D) and receptor-negative (MDA-MB-231, MDA-MB-468) human breast cancer cell lines. Immunocytochemical staining, flow cytometry, low-temperature electron paramagnetic resonance, and the Comet assay were used. Results: Upon treatment with lactoferrin, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Furthermore, LTF inhibits osteosarcoma cell proliferation and migration by regulating LRP1 and NF-kB p65 [25]. LTF can induce apoptosis and cause cell cycle arrest in breast cancer [26]. In addition, LTF inhibits epithelial-to-mesenchymal transition (EMT) and induces mesenchymal-to-epithelial transition (MET) in oral squamous cell carcinoma [24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LTF inhibits osteosarcoma cell proliferation and migration by regulating LRP1 and NF-kB p65 [25]. LTF can induce apoptosis and cause cell cycle arrest in breast cancer [26]. In addition, LTF inhibits epithelial-to-mesenchymal transition (EMT) and induces mesenchymal-to-epithelial transition (MET) in oral squamous cell carcinoma [24].…”
Section: Introductionmentioning
confidence: 99%
“…Organic dye Rhodamine 6G (R6G) and recombinant human lactoferrin [24,25] were used as analytes for the SERS measurements. The R6G dye (purchased from Sigma–Aldrich) and lactoferrin (received from the Department of Biochemistry of the Belarusian State University) had a 98% purity.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the lactoferrin detection in its water solutions is very important, as they can be used in the therapy of different diseases including cancer. Recently, it was reported that exogenous lactoferrin can affect the rate of tumor cells growth [24]. In addition, it was shown that recombinant human lactoferrin has a beneficial effect on the intestinal microflora, ultrastructure of the liver and intestines, activated lipid metabolism and steroidogenesis [25].…”
Section: Introductionmentioning
confidence: 99%
“…Comet assay. A standard classical method of alkaline gel electrophoresis of isolated cells was performed as described in [13]. Microscopic analysis was performed using a fluorescent microscope Axio Scope A.1 (Carl Zeiss, Germany).…”
Section: Design Of the In Vivo Experimentmentioning
confidence: 99%
“…An important feature of LF is its ability to bind to nucleic acids and to regulate cell cycle, proliferative activity of cells, and to affect the pro-and antioxidant balance in the cells. Human LF is a multifunctional glycoprotein that can inhibit cancer cells at G2/M phase [11,13].…”
mentioning
confidence: 99%